Fluoroquinolone Resistance Mechanisms and population structure of Enterobacter cloacae non-susceptible to Ertapenem in North-Eastern France - Guillard, Thomas; Cholley, Pascal; Limelette, Anne; Hocquet, Didier; Matton, Lucie; Guyeux, Christophe; Lebreil, Anne-Laure; Bajolet, Odile; Brasme, Lucien; Madoux, Janick; Vernet-Garnier, Véronique; Barbe, Coralie; et al. (Frontiers in Microbiology, 2015)
Fluoroquinolone (FQ) agents are a potential resort to treat infection due to Enterobacteriaceae producing extended spectrum β-lactamase and susceptible to FQ. In a context of increase of non-susceptibility to carbapenems among Enterobacteriaceae, we characterized FQ resistance mechanisms in 75 Enterobacter cloacae isolates non-susceptible to ertapenem in North-Eastern France in 2012 and describe the population structure by pulsed field gel electrophoresis (PFGE) and multilocus sequence typing (MLST). Among them, 14.7% (12/75) carried a carbapenemase-encoding gene. Except one isolate producing VIM-1, the carbapenemase-producing isolates carried the well-known IncL/M pOXA48a plasmid. Most of the isolates (59/75) harbored at least a FQ-R determinant. qnr genes were predominant (40%, 30/75). The MLST study revealed that E. cloacae isolates’ clonality was wide (24 different STs). The more widespread STs were ST74, ST101, ST110, ST114 and ST133. Carbapenem MICs were higher for E. cloacae ST74 than for other E. cloacae isolates. PMQR determinants were more often observed in E. cloacae ST74 isolates. These findings showed that (i) pOXA-48a is spreading in North-Eastern France, (ii) qnr is preponderant in E. cloacae, (iii) E. cloacae comprised a large amount of lineages spreading in North-Eastern France and (iv) FQ as an alternative to β-lactams to treat ertapenem non-susceptible Enterobacteriaceae are compromised.